First study of 237Np in Chinese soils: Source, distribution and mobility in comparison with plutonium isotopes. (August 2020) - Ni, Youyi; Guo, Qiuju; Huang, Zhaoya; Zheng, Jian; Li, Sixuan; Huang, Wenna; Bu, Wenting
Abstract: In this study, the distribution and migration of 237 Np and 239+240 Pu in soils in the vicinity (<5 km) of Qinshan and Tianwan Nuclear Power Plants in China were studied, which is the first specific study of global fallout 237 Np in Chinese soils. The 237 Np and 239+240 Pu concentrations in surface soils showed large spatial inhomogeneity. A remarkable 239+240 Pu concentration (4.783 mBq/g) was observed in a surface soil near Qinshan NPP and stands for the ever reported highest value in the Chinese soils. The inventories of 239+240 Pu in two Qinshan and Tianwan soil cores were estimated to be 128.8 Bq/m 2 and 121.0 Bq/m 2, respectively; while the 237 Np inventories were 0.039 Bq/m 2 and 0.035 Bq/m 2 at these sites, respectively. The 240 Pu/ 239 Pu atomic ratios in these soils indicated that the global fallout is the main source of Pu in these regions. However, the non-isotopic 237 Np/ 239 Pu atomic ratio in environmental soil is not a sensitive indicator for source identification. Furthermore, we conducted pilot study on the migration behaviors of 237 Np and 239+240 Pu in soil core at Qinshan site with the Convection-Dispersion Equation (CDE) model. The obtained apparent dispersion coefficients of 237 Np (2.82 ± 2.06 cm 2 /y) was 5 times higher than that of 239+240 Pu (0.57 ± 0.16 cm 2 /y), proving that 237 Np has stronger migration ability than Pu isotopes in the Qinshan soil. Finally, we predicted that with the increase of migration time, both 237 Np and 239+240 Pu concentration in the soil will gradually become more evenly distributed among different soil layers due to the dominant dispersion effects. Graphical abstract: Image 1 Highlights: First study of fallout 237 Np in soils near two Chinese NPPs was conducted. The highest fallout 239+240 Pu concentration in Chinese surface soil was found. In the soil core Np showed a "depleted" trend in contrast to Pu over time. Apparent dispersion coefficient of Np was higher than Pu in the soil core. Vertical distributions of Np and Pu will be more and more even in the future.